What Drives Customer Loyalty in Culinary Businesses - Arianto, Boby; Humairoh, Humairoh; Wijaya, Steven Surya (Universitas Muhammadiyah Tangerang, 2024)
Warunk Upnormal is renowned for its popularity as a favored dining establishment, thanks to its distinctive concept, inviting ambiance, and effective marketing techniques that contribute to its success. Currently, Warunk Upnormal is facing a contrasting situation, characterized by issues such as a decline in tourists, which has resulted in the closure of several of its stores. Hence, the author perceives that this phenomena indicates the presence of a disparity, which may serve as the foundation for this investigation. The objective of this study is to assess the impact of Food Quality, Price, Service Quality, Location, and Environment on Customer Loyalty by means of Customer Satisfaction at Warunk Upnormal. This study employs a survey methodology with a quantitative orientation. The data collection method employs a questionnaire. The Non Probability Sampling Technique was employed to collect samples, specifically using the Judgmental Sampling approach. These samples were disseminated to a total of 240 consumer respondents from Warunk Upnormal. The testing tool employs the SmartPLS software. The research findings indicate that all variables have been deemed valid and trustworthy, and satisfy the criteria for both Inner Model and Outer Model testing. The research findings indicate that Food Quality, Price, and Service Quality positively impact Customer Satisfaction, whereas Location and Environment have little impact on Customer Satisfaction. In addition, Customer Satisfaction has a beneficial impact on Customer Loyalty.